Adolescentes com diabetes Mellitus Tipo 1: construindo sentidos sobre adolescência, corpo, saúde e diabetes - Silva, Teresa Cristina Martins (2008)
The theme adolescent with Type 1 Diabetes Mellitus has been interest for many studies. Generally, investigations are inspired in the biomedical and biopsychosocial models of comprehending the health-disease process, which focus on the medical or other health services views. In this sense, the social constructionist perspective offers an alternative while privileging the patient, legitimizing him/her. Inspired by the constructionist proposal, this work aims to describe the interpretive repertoires used by adolescents with Type 1 Diabetes Mellitus in interviews on aspects related to Diabetes Mellitus and Adolescence. The theoretical-methodology was outlined on the qualitive methodology and the pretexts of Social Constructionism. Fourteen adolescents, aged 12 to 18, 7 girls and 7 boys, all diagnosed with Type 1 Diabetes Mellitus for at least a year and users of the City Center of Attention for Diabetics in the city of Uberlândia, MG Brasil, participated. The adolescents participated in a semi-structured interview which approached the following subjects: adolescence, body, health and diabetes. Data analysis was inspired in the proposal of the Discursive Practices Analysis which consists in the exhaustive reading of transcribed interviews, the construction of Idea Maps, and their vertical and horizontal analysis. In the first, interpretive repertoires were identified for each of the subjects investigated in their static character. In the second, mobility of the repertoires in their dynamic and contextual character were perceived. In vertical analysis, the following interpretive repertoires for each investigated subject were identified: Adolescence - (1) Adolescence altering the psychologic , (2) Adolescence that brings gains, (3) Adolescence: the other and I in interpersonal relationships, (4) The responsible adolescent; Body (1) Body in transformation, (2) Body and sexuality, (3) Esthetic Body, (4) Vulnerable Body; Health (1) Health and self-care, (2) Controlled Health, (3) Health as disposition, (4) Heath is everything ; Diabetes (1) Diabetes as a problem, (2) Diabetes as a disease, (3) Diabetes as an experience. Horizontal analysis demonstrated how the repertoires are combined to describe, justify, explain and to position oneself in different situations, observing the dynamic and contextual character of the same situations. This analysis made it possible to show the diversity of available repertoires for the understanding of the adolescence diabetes relationship as many of them are beyond the traditional concepts spread by the dominant scientific discourse. Some repertoires seem to produce descriptions endowed with positivity that help the adolescent live with the disease; however, others generate descriptions that seem to be difficult and painful for them. Therefore, it is necessary that the available repertoires for understanding adolescence and diabetes, which make the care for diabetes easier, gain strength and be considered by health professionals and so including the adolescent as an active participant in the construction of the therapeutic project.